PENGARUH EKONOMI ORANG TUA DAN KECERDASAN EMOSIONAL TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 7 KABUPATEN TEBO - Pratiwi Indah Sari, Benar Sembiring (Universitas Batanghari Jambi, 2017)
This study aims to determine the description of the parents economy, emotional intelligence, student learning motivation, and the influence of parents' economy and emotional intelligence on student learning motivation on economic subjects in SMA Negeri 7 Kabupaten Tebo. The results explain that the economic variables of parents and motivation to learn are in good category, while emotional intelligence variables are in good enough category. Meanwhile, the parent economic and emotional intelligence both partially and simultaneously have a positive value and have a significant effect on student learning motivation on economic subjects in SMA Negeri 7 Kabupaten Tebo. That is, with an adequate level of economic parents and accompanied by emotional kecerdaasan students in dealing with the environment then it will provide widespread opportunities for students to explore themselves so that ultimately will lead to a motivation (motivation) to learn more optimal.Kata Kunci : Economics of Parents, Emotional Intelligence, Learning Motivation